Gênero notícia: modalidade, polidez e ethos nas eleições presidenciais 2006 - Nunes, Viviane Bossan (2007)
The discussion about the manipulation exerted by communication vehicles gets more and more space in society. In spite of that, some genres, especially those belonging to the so-called informative journalism, still have a lot of prestige once they are believed to pursuit impartiality. Nevertheless, language itself and the decision making imposed by it do not allow an effectively neuter positioning, hence any enunciation reflects human experiences and social ideologies. This research aims the analysis of language constructions characterized as modality, politeness and ethos in news published in the newspaper Folha de S. Paulo during the covering of the presidential elections in 2006. Such investigation intends to stand out linguistic aspects which can be used to lead the reader s opinion according to the newspaper company. We also pointed out ideologies able to institute social and group identities and establish belonging criteria to these groups based on goals, values and behavior. The theoretical current used is the Critical Discourse Analysis of Fairclough. The linguistic units analysis in the newspaper discourse was initiated with the reading of the texts selected from the collection of the public library Mário de Andrade in which we picked out examples of modality, politeness and ethos. We pointed out the influence of ideological traces, present in the newspaper company and in the society, in the options and selections the writer is supposed to make and how it materializes in the language used in news. The results indicate the manifestation of particular ideologies and subjectivity in the news, although it is considered a genre belonging to informative journalism, in which supposedly there is a commitment to objectivity